PROGRAM PENGEMBANGAN OBJEK WISATA SILOKEK DI KABUPATEN SIJUNJUNG PROVINSI SUMATERA BARAT - Atdrian " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
has a lot of tourism potential, the potential fine nature, culture, history and others. One of the potential that has good prospects for development are attractions silokek contained in kenagarian silokek. But very unfortunate slowness of morement arts and culture tourism department of youth and sports so that there is untapped potential optimally. Seeing this attraction facilities and infrastructure provided is not adequate, there is still a lack of promotion of tourist attraction, and the lack of cooperation with the private sector. Tourism agency youth cultural arts and sports sijunjung design a program to develop the tourist area into a tourist destination silokek. This research aims to determine the tourism development program silokek in Sijunjung and the factors that affect the tourism development program Silokek sijunjung in the province of west sumatra.The theory used is the theory nakamura and smallwood in sujianto namely the implementation of the program from the aspect of compliance officers subordinate to superiors, the functioning of routine procedures, achievement objectives. In this reserch the auther uses descriptive qualitative research methods with research sites in the arts and culture tourism department of youth and sports sijunjung and that became a key informant was the head of the field of tourism, data collection techniques such as interview, observation, adn documentation. And data analysis program used by the tourism department of arts and culture of youth and sports and then analyzed what are the factors that affect the tourism development program silokek supported by interview conducted by the researchers then conclude.From the result of this research note that tourisms development program undertaken silokek art and culture tourism department of youth and sports is not maximum, tourism office of the youth cultural atrs and spotrs its own coordination between subordinates and superiors is still not going well. In addition of procedures or given still not maximized due to indiscipline staff of civil servants and not achieving the objectives of the program silokek, budget/funding, lack of quantity and quality of its human resources deparment of tourism culture art youth and sports as well as in the area of land acquisition constraints silokek.